Nutrient optimization for indigenous microbial consortia of a Bhagyam oil field: MEOR studies - Sharma, Neha; Lavania, Meeta; Koul, Vatsala; Prasad, Dhruva; Koduru, Nitish; Pandey, Amitabh; Raj, Rahul; Kumar, M. Suresh; Lal, Banwari (Frontiers in Microbiology, 2023)
The microbial enhanced oil recovery (MEOR) method is an eco-friendly and economical alternative technology. The technology involves a variety of uncertainties, and its success depends on controlling microbial growth and metabolism. This study is one of a kind that showed successful tertiary recovery of crude oil through indigenous microbial consortia. In this study, a medium was optimized to allow ideal microbial growth under reservoir conditions through RSM. Once the nutrient recipe was optimized, the microbial metabolites were estimated through gas chromatography. The maximum amount of methane gas (0.468 mM) was produced in the TERIW174 sample. The sequencing data set showed the presence of Methanothermobacter sp. and Petrotoga sp. In addition, these established consortia were analyzed for their toxicity, and they appeared to be safe for the environment. Furthermore, a core flood study showed efficient recovery that was 25 and 34% in TERIW70 and TERIW174 samples, respectively. Thus, both the isolated consortia appeared to be suitable for the field trials.